Recent Stressful Life Events in Euthymic Major Depressive Disorder Patients: Sociodemographic and Clinical Characteristics - Gianluca Serafini; Gianluca Serafini; Xenia Gonda; Xenia Gonda; Xenia Gonda; Giovanna Canepa; Giovanna Canepa; Pierre A. Geoffroy; Pierre A. Geoffroy; Maurizio Pompili; Mario Amore; Mario Amore (Frontiers in Psychiatry, 2020)
BackgroundStressful life events (SLE) may influence the illness course and outcome. This study aimed to characterize socio-demographic and clinical features of euthymic major depressive disorder (MDD) outpatients with SLE compared with those without.MethodsThe present sample included 628 (mean age=55.1 ± 16.1) currently euthymic MDD outpatients of whom 250 (39.8%) reported SLE and 378 (60.2%) did not.ResultsAfter univariate analyses, outpatients with SLE were most frequently widowed and lived predominantly with friends/others. Moreover, relative to outpatients without SLE, those with SLE were more likely to have a family history of suicidal behavior, manifested melancholic features, report a higher Coping Orientation to the Problems Experienced (COPE) positive reinterpretation/growth and less likely to have a comorbid panic disorder, residual interepisodic symptoms, use previous psychiatric medications, and currently use of antidepressants. Having a family history of suicide (OR=9.697; p=≤.05), history of psychotropic medications use (OR=2.888; p=≤.05), and reduced use of antidepressants (OR=.321; p=.001) were significantly associated with SLE after regression analyses. Mediation analyses showed that the association between current use of antidepressants and SLE was mediated by previous psychiatric medications.ConclusionHaving a family history of suicide, history of psychotropic medications use, and reduced use of antidepressants is linked to a specific “at risk” profile characterized by the enhanced vulnerability to experience SLE.